Effects of confidence and social benefits on consumers' extra-role and in-role behaviors: A social identity and social exchange perspective. (March 2022) - Utkarsh,; Gupta, Roopak Kumar
Abstract: This study explores the effects of relational benefits on consumers' extra-role (civic virtue) and in-role (consumer loyalty) behaviors from social identity and social exchange perspectives, in addition to the mediating role of consumer–company identification (CCI) and perceived value. Structural equation modeling was used to analyze the data obtained from a cross-sectional survey of 254 consumers. The findings reveal that relational benefits promote consumers' extra-role and in-role behaviors. Specifically, confidence and social benefits, directly and indirectly, affect civic virtue and consumer loyalty. Supporting our integrative framework, the results demonstrate that CCI mediates the effect of confidence and social benefits on civic virtue and consumer loyalty, whereas perceived value only mediates the relationship between confidence and social benefits and consumer loyalty. This study presents important implications for academicians and practitioners. Highlights: The study explores the effects of relational benefits on extra-role and in-role behavior of consumers. Investigates the mediating role of CCI and perceived value between relational benefits and extra-role and in-role behavior. Relational benefits promote consumers' extra-role and in-role behaviors. Identity-based path is more crucial than value-based path in promoting consumers' extra-role behavior.